2020
DOI: 10.1002/arch.21669
|View full text |Cite
|
Sign up to set email alerts
|

Association between olfactory sensitivity and behavioral responses of Drosophila suzukii to naturally occurring volatile compounds

Abstract: Drosophila suzukii Matsumura (Diptera: Drosophilidae) is an invasive, destructive crop pest that originated in South East Asia. D. suzukii recently invaded Western countries and is threatening both European and American fruit industries. It is extremely attracted to otherwise undamaged, ripening fruits, unlike most other Drosophila species that attack only decaying or rotten fruits. Recent studies on different insect species showed that several naturally occurring compounds of easy market availability showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The olfactory responses of Mahanarva spectabilis to forage VOCs suggested that menthone, eucalyptol and camphor were all compounds likely to cause loss of attractiveness or repellence ( Silva et al., 2019 ). Menthol exhibited moderate repellent effects on Drosophila suzukii ( Corda et al., 2020 ). Compared with A-phase, the unique decanal in Ficus pumila var.…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory responses of Mahanarva spectabilis to forage VOCs suggested that menthone, eucalyptol and camphor were all compounds likely to cause loss of attractiveness or repellence ( Silva et al., 2019 ). Menthol exhibited moderate repellent effects on Drosophila suzukii ( Corda et al., 2020 ). Compared with A-phase, the unique decanal in Ficus pumila var.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, the ability to identify mating partners, oviposition sites and food sources is strongly influenced by information arising from their chemical senses, olfaction and taste [1][2][3][4][5][6][7][8][9][10][11][12][13]. In both vertebrates and invertebrates-chemosensory performance varies among organisms belonging to the same species, and this diversity depends on age, sex, physiological state, diet, population, habitat and genetic factors [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%